Method for multi-information drilling detection after mining disasters. (September 2020) - Zheng, Xuezhao; Wang, Hu; Guo, Jun; Zhang, Duo
Highlights: l A software system for the simultaneous acquisition and transmission of audiovisual and environmental parameters was developed. l The multimedia communication circuit is designed to realize the intrinsic safety of the detection system. l Through the application of mine disaster site rescue, the reliability and practicability of the device were tested. Abstract: The underground environment of a disaster-stricken mining area is complex, dangerous, and of limited space. Despite its frequent use above ground, communication and detection technology is not adaptable to underground conditions. After the mine accident, the communication between the disaster area and the ground was almost paralyzed, and it was difficult for rescuers to find the location of the underground accident and accurately locate the trapped miners. As a result, the rescue work is often blind and random, which significantly hampers rescue progress and can result in failure. Given this situation, this study used the key technologies of multi-media information collection, synchronous transmission, and underground explosion-proof facilities as a basis for the research and development of a multi-information drilling detection device. This device is designed to transmit wireless signals or wired signals that convey crucial data, such as images, sounds, and environmental gas concentrations. With long-distance real-time data transmission, the apparatus can collect multiple sources of information to assist searches for underground trapped persons, fault diagnosis of rescue boreholes, and underground environmental detection. Application of this device was tested on site and found to enable reliable in-situ information to be generated for use by experts and for rescue commands. Graphical abstract: Using multiple life information detection devices to detect people in vertical drilling of coal mines. Image, graphical abstract